Cleaved N-terminal histone tails distinguish between NADPH oxidase (NOX)-dependent and NOX-independent pathways of neutrophil extracellular trap formation - Pieterse, Elmar; Rother, Nils; Yanginlar, Cansu; Gerretsen, Jelle; Boeltz, Sebastian; Munoz, Luis Enrique; Herrmann, Martin; Pickkers, Peter; Hilbrands, Luuk B.; Van Der Vlag, Johan (Annals of the Rheumatic Diseases, 2018)
OBJECTIVES: Neutrophil extracellular traps (NETs) act in various rheumatic diseases. Although NET formation was originally described as a nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX)-dependent pathway, it appears that there are also NOX-independent pathways of NET release. Currently, no tools are available that can discriminate between both NET-forming pathways. We aimed to develop a serological method allowing the discrimination between NETs generated through NOX-dependent or NOX-independent pathways. METHODS: Histones from in vitro generated NOX-dependent and NOX-independent NETs were characterised with a panel of lupus-derived antibodies against N-terminal histone tails using immunofluorescence microscopy, western blot and ELISA. NETs in patients with NET-associated diseases, that is, rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), psoriatic arthritis (PsA) and sepsis, were characterised in sandwich ELISAs employing antibodies against myeloperoxidase (MPO) and N-terminal histone tails as detecting and capturing antibodies, respectively. Functional responses of endothelial cells to NOX-dependent and NOX-independent NETs were assessed as well. RESULTS: Neutrophil elastase cleaves the N-terminal tails of core histones during NOX-dependent, but not during NOX-independent NET formation. Consequently, the detection of MPO-histone complexes with antibodies against N-terminal histone tails allows discrimination between NETs formed through a NOX-dependent or NOX-independent manner. Characterisation of in vivo circulating NETs revealed the presence of NOX-independent NETs in RA, SLE and sepsis, but NOX-dependent NETs in PsA. NOX-independent NETs displayed an increased capacity to activate endothelial cells when compared with NOX-dependent NETs. CONCLUSIONS: These results indicate heterogeneity in NET-forming pathways in vivo and highlight the need for disease-specific strategies to prevent NET-mediated pathology.
EVALuna2:34475